Share

Prove That: 1/(1+X^(B-a)+X^(C-a))+1/(1+X^(A-b)+X^(C-b))+1/(1+X^(B-c)+X^(A-c))=1 - CBSE Class 9 - Mathematics

ConceptLaws of Exponents for Real Numbers

Question

Prove that:

1/(1+x^(b-a)+x^(c-a))+1/(1+x^(a-b)+x^(c-b))+1/(1+x^(b-c)+x^(a-c))=1

Solution

Consider the left hand side:

1/(1+x^(b-a)+x^(c-a))+1/(1+x^(a-b)+x^(c-b))+1/(1+x^(b-c)+x^(a-c))

=1/(1+x^b/x^a+x^c/x^a)+1/(1+x^a/x^b+x^c/x^b)+1/(1+x^b/x^c+x^a/x^c)

=1/((x^a+x^b+x^c)/x^a)+1/((x^b+x^a+x^c)/x^b)+1/((x^c+x^b+x^a)/x^c)

=x^a/(x^a+x^b+x^c)+x^b/(x^b+x^a+x^c)+x^c/(x^c+x^b+x^a)

=(x^a+x^b+x^c)/(x^a+x^b+x^c)

= 1

Therefore left hand side is equal to the right hand side. Hence proved.

Is there an error in this question or solution?

APPEARS IN

RD Sharma Solution for Mathematics for Class 9 by R D Sharma (2018-19 Session) (2018 to Current)
Chapter 2: Exponents of Real Numbers
Ex. 2.10 | Q: 4.2 | Page no. 12

Video TutorialsVIEW ALL [1]

Solution Prove That: 1/(1+X^(B-a)+X^(C-a))+1/(1+X^(A-b)+X^(C-b))+1/(1+X^(B-c)+X^(A-c))=1 Concept: Laws of Exponents for Real Numbers.
S